Research progress of assessment of diet adherence among patients with ulcerative colitis (溃疡性结肠炎患者饮食依从性评估研究进展) - XU Jingjin (徐京巾); TANG Ling (唐玲); LI Ye (李野) (Journal of International Translational Medicine Limited, 2022)
This paper summarized the research progress of objective and subjective tools for assessing diet adherence among patients with ulcerative colitis at home and abroad, and detailed information about contents of included evaluation scales was provided. Given the imperfect tools which are currently used in practice, efforts should be made to form an assessment scale of diet adherence according to the food preference in domestic population, in order to provide more suitable tools for clinical practitioner. (本文总结了溃疡性结肠炎患者饮食依从性的国内外评估量表, 包括客观评价量表和主观评价量表, 并详细介绍了各个量表具体内容。针对国内缺乏相关成熟量表的情况, 应结合我国人群饮食偏好形成溃疡性结肠炎患者饮食依从性量表, 为临床评估和治疗提供评估工具。)